Pembentukan Karakter Siswa di SMA N 12 Semarang - Nur Cholifah (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
In the era of globalization, social media plays a great role in influencing students’ development. This influence tends to be a negative impact in which they easily imitate some negative actions such as doing student brawls, using and selling drugs, committing criminal acts, etc. These negative attitudes need to be handled and anticipated. One that can be proposed to overcome this problem is through the character education program. This program can be inserted into the Civics subject at school in which the Civics teachers play the main role as the leader of this character education. This type of research is descriptive qualitative. This research was conducted at SMA Negeri 12 Semarang. The results of the study show that the efforts of Civics teachers in shaping the character of students at SMA Negeri 12 Semarang are making learning devices in which there are character values, through active learning, in learning activities character values are inserted, Civics teachers become models and make themselves examples. for students as teachers of character. Some of them are such as emphasizing approaches to students through good communication with students, through independent assignments outside school hours by observing problems that are developing in the community so that students have concern for the surrounding environment and become critical in solving a problem. In addition, Civics teachers emphasize discipline to students.